THE CONCEPT OF PEDAGOGICAL TECHNOLOGY, ITS DEFINITIONS AND DIFFERENCES FROM THE METHODOLOGY - Dilfuza Mahmudovna Rakhmonova (International Journal on Integrated Education, 2022)
the article discusses the concept of pedagogical technology, while analyzing its differences from tariffs and methodology using examples.